2011
DOI: 10.1016/j.ajpath.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αv Expression Is Required for the Acquisition of a Metastatic Stem/Progenitor Cell Phenotype in Human Prostate Cancer

Abstract: Integrins participate in multiple cellular processes, including cell adhesion, migration, proliferation, survival, and the activation of growth factor receptors. Recent studies have shown that expression of ␣v integrins is elevated in the prostate cancer stem/progenitor cell subpopulation compared with more differentiated, committed precursors. Here, we examine the functional role of ␣v integrin receptor expression in the acquisition of a metastatic stem/progenitor phenotype in human prostate cancer. Stable kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…In line with the miR-25 data presented in this study, we previously found that a v -integrins play a pivotal role in the acquisition of a migratory stem/progenitor phenotype, tumorigenicity and the formation of distant bone metastasis in vivo (31,45). Moreover, a 6 b 4 integrin expression has already been associated with prostate cancer invasion, metastasis, and disease progression (46)(47)(48).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In line with the miR-25 data presented in this study, we previously found that a v -integrins play a pivotal role in the acquisition of a migratory stem/progenitor phenotype, tumorigenicity and the formation of distant bone metastasis in vivo (31,45). Moreover, a 6 b 4 integrin expression has already been associated with prostate cancer invasion, metastasis, and disease progression (46)(47)(48).…”
Section: Discussionsupporting
confidence: 62%
“…Previously, we have shown that ITGAV is required for the acquisition of a stem/progenitor phenotype (31). In addition, ITGAV and ITGA6 are highly expressed in prostate progenitor cells and ITGA6 has been established as maker for progenitor cells in prostate and breast cancer.…”
Section: Rac1 (Fig 2c-e Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin ␣ V expression is required for the acquisition of a cancer metastatic stem or progenitor cell phenotype ( 31 ). Transcriptional silencing of ␣ V and ␤ 3 integrin subunits suppresses cancer metastasis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATTC characterized the cell lines using short tandem repeat profiling. PC3-derived PC3-M-Pro4luc cells (15) and LNCaP-derived cell lines C4-2 and C4-2 B were grown in DMEM and T-Medium, respectively. For FACS, primary antibodies included AIIB2 anti-human integrin b1, 4A10 anti-human integrin a2, and sc-18849 antihuman CD44 (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%